The Strategy of Distribution Management - Christopher Martin (Butterworth Heinemann, 1986)
Preface, The Total Distribution Concept, The Corporate Role of Logistics, Customer Service and Marketing, The Cost of Distribution, Auditing Distribution Performance, Logistics Information Systems, Distribution Requirements Planning, Distribution and Supply Channel Strategy, Developing the Distribution Plan, Implementing Logistics Strategy, Index.
Preface, The Total Distribution Concept, The Corporate Role of Logistics, Customer Service and Marketing, The Cost of Distribution, Auditing Distribution Performance, Logistics Information Systems, Distribution Requirements Planning, Distribution and Supply Channel Strategy, Developing the Distribution Plan, Implementing Logistics Strategy, Index.